Hepatitis due to Epstein-Barr virus and cytomegalovirus: clinical features and outcomes. - Leonardsson, Hilmar; Hreinsson, Jóhann Páll; Löve, Arthur; Björnsson, Einar S (Scandinavian Journal of Gastroenterology, 2017)
To access publisher's full text version of this article click on the hyperlink below To determine the frequency of cytomegalovirus (CMV) and Epstein-Barr virus (EBV) hepatitis among those with acute CMV and EBV infection in a population based setting and to compare these two types of hepatitis and analyze the outcomes. A retrospective search was undertaken on all patients with IgM antibodies to CMV and EBV during the period of 2006-2015 in the virological database of the University Hospital of Iceland covering the metropolitan area of Reykjavík (population 202,255). Patients with available liver tests at the University Hospital and/or admitted to this institution were included and relevant clinical data obtained from medical records. Overall, 190 patients had acute EBV infection during the study period and 118 patients were diagnosed with acute CMV. Overall, 82% of patients with acute EBV infection had hepatitis, males 43%, median age 17 years, 15% had jaundice and 26% hospitalized. Among those with acute CMV infection, 69% had elevated liver tests, 63% males, median age 33 years, 9% had jaundice and also 26% hospitalized. Overall, 17% of those with CMV hepatitis were immunosuppressed, 6% were pregnant and 4% developed Guillain-Barré syndrome following the infection. A high proportion of patients with acute CMV and EBV developed hepatitis and jaundice, most of those patients have good prognosis. Patients with CMV hepatitis were more often immunosuppressed, required hospitalization or were pregnant in comparison with patients with EBV hepatitis.